2018
DOI: 10.1094/mpmi-07-17-0193-r
|View full text |Cite
|
Sign up to set email alerts
|

An NMRA-Like Protein Regulates Gene Expression in Phytophthora capsici to Drive the Infection Cycle on Tomato

Abstract: Phytophthora spp. cause devastating disease epidemics on important crop plants and pose a grave threat to global crop production. Critically, Phytophthora pathogens represent a distinct evolutionary lineage in which pathogenicity has been acquired independently. Therefore, there is an urgent need to understand and disrupt the processes that drive infection if we aspire to defeat oomycete pathogens in the field. One area that has received little attention thus far in this respect is the regulation of Phytophtho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…infestans (Ah-Fong et al, 2017a). NMRA also was proposed to control the transcription of late-induced effectors in Phytophthora capsici (Pham et al, 2018). Spiking at the same time are mRNAs for genes used to assimilate nitrate, which is a nonpreferred nitrogen source compared with amino acids (Abrahamian et al, 2016).…”
Section: Oomycetes Have An Exit Strategymentioning
confidence: 99%
“…infestans (Ah-Fong et al, 2017a). NMRA also was proposed to control the transcription of late-induced effectors in Phytophthora capsici (Pham et al, 2018). Spiking at the same time are mRNAs for genes used to assimilate nitrate, which is a nonpreferred nitrogen source compared with amino acids (Abrahamian et al, 2016).…”
Section: Oomycetes Have An Exit Strategymentioning
confidence: 99%
“…Since the structure of NmrA was resolved, researchers have discovered several NmrA-like proteins which are able to bind coenzymes NAD(H) or NADP(H) but lack the function of dehydrogenation, including PadA from Dictyostelium discoideum , QOR2 from Escherichia coli , PcNMRAL1 from Phytophthora capsica [ [5] , [6] , [7] ]. While NmrA and the majority of NmrA-like proteins are identified in bacteria or fungi, HSCARG, which is also known as NMRAL1, is widely present in higher animals.…”
Section: Introductionmentioning
confidence: 99%
“…The same expression profiles were observed in early and late rye media cultures (Fig 10B). As this paper was being written, a microarray study of Phytophthora capsici infecting tomato was published [48]. Our analysis of data from that paper deposited in ArrayExpress showed that the patterns of NR and NMRA expression in Ph .…”
Section: Resultsmentioning
confidence: 99%
“…capsici were obtained from ArrayExpress accession E-MTAB-5620. Reported in Results are the median-normalized expression values from 8 and 24 hr dpi, based on three biological replicates [48]. Expression of the Hmp1 , Npp1 , and Cdc14 marker genes indicated that these timepoints represent biotrophic and necrotrophic stages similar to the early and late tuber timepoints described for Ph .…”
Section: Methodsmentioning
confidence: 99%